Reforming specialized inspection procedures to improve business environment in vietnam for trade facilitation implementation - Nga Le Thi Viet; Huy Dinh Tran Ngoc; Hang Nguyen Thi; Lan Leng Thi; Thach Nguyen Ngoc (Management)
our study aims to analyze and assess the process of reforming the specialized inspection procedures in Vietnam which is included in Vietnam’s trade facilitation implementation program, and suggesting some recommendations for Vietnam to do the reform to improve business environment and enhance Vietnam’s national competitiveness. By synthesizing and analyzing secondary data from creditable sources such as World Bank, UNESCAPE, UNCTAD, WTO, VCCI, General Department of Vietnam Customs, as well as interviewing officials from Ministry of Industry and Trade of Socialist Republic of Vietnam, etc.